Why does multiple sclerosis only affect human primates?. (April 2016) - 't Hart, Bert A
Background: Multiple sclerosis (MS) develops exclusively in humans. Non-human primates are resistant against MS, although they are highly susceptible to the MS animal model, experimental autoimmune encephalomyelitis (EAE). Unravelling of the cause(s) underlying this discrepancy is highly relevant as insights might be gained into the elusive event(s) that trigger(s) MS. A well-established difference between the human primate ( Homo sapiens ) and non-human primates is that humans are unable to synthesize the sialic acid N-glycolylneuraminic acid (Neu5Gc). Viewpoint: We propose the concept that long-term ingestion by human primates of the foreign Neu5Gc, via red meat consumption, is an ignored environmental risk factor for MS. Conceptually, incorporation of dietary Neu5Gc into vital regions of the central nervous system, such as the blood–brain barrier (BBB) and the axon–myelin unit, creates targets for binding of de novo synthesized heterophilic anti-NeuGc antibodies. Binding of the antibodies can cause BBB leakage and destabilization of the axon–myelin coupling. The ensuing cytodegeneration and release of self-antigens could be a start of the characteristic pathological features of MS.